THE RELATIONSHIP BETWEEN MATERNAL AND CHILD HEALTH SERVICES WITH THE PREVALENCE OF STUNTING BASED ON THE BASIC HEALTH RESEARCH IN INDONESIA - Demsa Simbolon; Dhea Adevianti; Luluk Setianingsih; Lisma Ningsih; Lusi Andriani (The Indonesian Journal of Public Health, 2021)
ABSTRACTStunting is a linear growth disorder considered as a serious health problem in Indonesia, where its prevalence is related to maternal and child health (MCH) services. This study aimed to compare the coverage of maternal and child health services between two surveys and analyze how they relate to the prevalence of stunting. The study used aggregate data from the 2013 and 2018 Basic Health Research Reports using a cross-sectional approach. The research sample spanned to 34 provinces in Indonesia. Stunting prevalence was taken as aggregate data from individuals based on height-for-age z-scores (HAZ). The independent variable was the achievement of MCH service indicators. Data analysis used variance measures, correlations, simple linear regression, and paired T-tests. The results found variations in the prevalence of stunting, with 25.4% in 2013 and 25.1% in 2018. There was a 7.4% decrease in severe stunting prevalence between 2013 and 2018, but the decrease was not significant (p = 0.506). The analysis results of the 2013 Basic Health Research showed that MCH service indicators related to stunting prevalence were coverage of antenatal care, iron consumption, delivery by health personnel, delivery in health facilities, postpartum maternal health services, low birth weight (LBW) prevalence, neonatal examination, complete immunization, health card ownership, and growth monitoring. The analysis results of the 2018 Basic Health Research showed that MCH indicators were related to the prevalence of antenatal care coverage, delivery by health personnel, and delivery in health facilities, postpartum maternal health services, LBW prevalence, neonatal examination, and complete immunization. There was a significant increase in the coverage of MCH services from 2013 and 2018 (p < 0.0001), except for the coverage of Fe tablet consumption, the prevalence of stunted birth babies, ownership of health cards, provision of vitamin A, and provision of colostrum. The better the coverage of MCH services, the lower the stunting prevalence. Efforts to improve the MCH service programs are required to reduce the prevalence of stunting for Indonesian children. Keywords: stunting, children under five years old, coverage of maternal and child health services